Rhinolithiasis: lesion specificities of the first case described in Togo - Amana, Bathokedeou; Foma, Winga; Pegbessou, Essobozou; Lawson, Stephen Lionel Antoine; Dolou, Warou; Boko, Essohanam; Kpemissi, Eyawèlohn (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Rhinolithiasis is a solid concretion by progressive deposition of calcareous salts around an endogenous or exogenous central body, resorbable or not, of variable shape and sizes. Its diagnosis is based on endoscopic nasal examination completed by a computed tomography (CT) of the naso-sinus cavities. We are reporting the first described case of rhinolithiasis in Togo, particularly remarkable for its association with septal perforation, nasal mycosis, and granulomatous reaction.